Power Analysis of 3 Phase Induction Motor Drive Conveyor 06 at PT. Mitrabara Adiperdana: Analisis Daya Motor Induksi 3 Fasa Penggerak Conveyor 06 di PT. Mitrabara Adiperdana - abdul muis prasetia; Linda Sartika; Hironimus (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
Conveyor belt is a material handling tool that is widely used in minning industry. The tool consists of belts or tires made of various types of materials that are resistant to the transportation of solid objects or coal. In order to drive the conveyor, a 3-phase induction motor is needed. PT. Mitrabara Adiperdana used induction motors on each conveyor including conveyor 06. With consumer demand, motors continue to operate to drive conveyors in transporting coal on stockpiles filling barges. The number of berges filled makes the motor continue to operate to move the conveyor for up to one full day. Therefor, it is necessary to analyze the power of consumption and performance level of the motor on conveyor 06, because if there is demage to the motor, the production process on conveyor will be hampered. From the primary data obtained in the field by making direct measurements and obtained the calculation results, the power value is 35.058 Kw when the conveyor is not loaded and 81.80 kw when the conveyor is loaded. With the result of power used when loaded, the calculation of efficiency is 69,45%. Whith this value, the conveyor motor 06 operates less effectively. It is stated be effective when the efficiency value is between 80% and 100% of the effeciency value on motor rating rate.